Iron deficiency anemia - Orlicz-Szczęsna, Grażyna; Żelazowska-Posiej, Justyna; Kucharska, Katarzyna (Current Problems of Psychiatry, 2012)
Iron deficiency anemiais the mostcommon type ofanemia. It canresult fromexcessive loss ofiron, poor absorption, inadequate supplyor an increaseddemand forthis element. Anemiais particularly common indeveloping countries. A largenumber of the population is exposed to its occurrence, especially infants, children, people inthe age of puberty, pregnant women, the elderly and patientswith eating disorders. Iron deficiencyanemiais recognizedon the basisof laboratory tests - blood count, assessment of iron metabolism parameters andsometimes bone marrow biopsy. Determination of low levels of ironobligesto performadditional teststo findits cause, and also to differentiatewith otheranaemias, causingsimilarmorphological changes. Oral and intravenousmedications are available in the treatment of iron deficiency anemia.